ผลของโปรแกรมการจัดการตนเองของบุคคลและครอบครัวต่อภาวะน้ำเกินในผู้สูงอายุโรคไตวายเรื้อรังที่รับการฟอกเลือดด้วยเครื่องไตเทียม - ธนัยรัตน์ รุ้งพราย (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
This research is a quasi-experimental study. The purpose of study was to test the effect of an individual and family self-management program in older persons with chronic kidney disease (CKD) and underwent hemodialysis. Simple random sampling technique from a dialysis unit in medical development clinic was used to recruit 40 persons diagnosed CKD aged 60 years old and above. All patients were divided into two equal groups and they were 20 in an experimental group and 20 patients in a control group. The experimental group received the individual and family self-management program while the control group received conventional care program for 4 weeks. Both groups were matched with similar characteristics as age, gender, and incomes. The instrumentations were the individual and family self-management program. The data collection was documented by demographic questionnaires and interdialytic weight-gained record. Data were reported in mean, standard deviation, percentage and they were analyzed by t-test. The results were as following. 1. The mean value of volume overload in CKD patients was significant lower in the patients who received the individual and family self-management program compared to before receiving the program at the significant level of .05 2. The mean value of volume overload in CKD patients who were used the individual and family self-management program was significant lower than the patients who received a conventional program at the significant level of .05